DOES SHG PROGRAM ALLEVIATE POVERTY? EVIDENCE FROM FOUR CLUSTERS IN SEMI-URBAN REGIONS OF INDIA - Saravanan, Sivagandhi (The European Journal of Applied Economics, 2017)
The paper suggests that microfinance program has significantly improved the standard of living of the poor people. The datasets from 367 SHG members and 178 non-SHG members are taken into analysis. Simultaneous equation method is applied to observe the effect of exogenous variables on the endogenous variable. Income and asset are endogenous variables, which have significant impacts on each other. Age, education and village infrastructure have positive impacts on both income and asset.
Keywords: poverty; microfinance; control; treatment; simultaneous equation